Kajian Implementasi Landasan Religius dengan Peran Kepala TK dalam Membentuk Karakter Anak Usia Dini - Sune, Mistawati; Isa, Abd. Hamid (Irfani, 2026)
Early childhood education plays an important role in shaping children’s character, morality, and spirituality during the early stages of development. The cultivation of religious values in kindergarten is not only carried out through formal religious activities but also through the habituation of positive behaviors in daily learning activities. In addition to the role of teachers, the leadership of the kindergarten principal also influences the implementation of religious values and the development of a school culture that supports children’s character formation. This study aims to analyze the implementation of a religious foundation in kindergarten learning and to examine the role of the kindergarten principal in supporting the character development of early childhood students. This research employed a qualitative approach with a descriptive design. Data were collected through classroom observations, interviews with teachers, and document analysis of learning plans such as the Daily Learning Implementation Plan (RPPH). The results show that religious values are implemented through daily habituation activities such as collective prayers, greeting practices, lining up before entering the classroom, sharing with peers, and maintaining environmental cleanliness. These values are also integrated into lesson planning. The principal plays a role in guiding teachers, establishing school policies, conducting learning supervision, and encouraging parental involvement. These practices contribute to the development of children’s character, including discipline, empathy, politeness, responsibility, and honesty. Therefore, consistent implementation of religious values supported by effective school leadership can strengthen positive character development in early childhood education.